Nutritional Efficiency of Eucalyptus Clones Under Water Stress - Müller,Caroline (2017)
Abstract Plant health and nutrition are strongly influenced by the availability of water. The objective of this study was to evaluate the different patterns of initial growth and nutritional efficiency of ten drought-stressed Eucalyptus clones. Water stress conditions were induced by osmotic stress, by gradual addition of polyethylene glycol 6000 over a 20-day period. Drought stress significantly reduced the dry matter of leaves, roots, and the whole plant as well as the nutritional efficiency of most clones. Clone PL040 was the least efficient in nutrient uptake and use and the most sensitive to drought stress. Interestingly, under drought stress, the drought-tolerant clones generally had high AE (absorption efficiency), but low nutrient UE (use efficiency), whereas the sensitive clones had low AE and low UE for root formation and high AE for leaf formation. In a combined evaluation of growth and nutrient use efficiency, the clones vc865, i182, i144, and gg157 were grouped as drought-tolerant; 1528 and i224 as moderately tolerant; and 1641, 3367, i042, and PL040 as drought-sensitive.